Pre-surgical physical therapy treatment in adult with late diagnosis of bilateral Bochdalek's hernia: a case study (Research, Society and Development, 2022)
Bochdalek's Hernia (BH) is characterized by a defect in the posterolateral diaphragmatic foramen leading to evisceration of the abdominal contents into the thoracic cavity. The treatment is provided, according to the extent of the hernia and the degree of involvement of the structures, through a simple surgery by videolaparoscopy or, in more severe cases, the use of polypropylene meshes for the repair. The aim of the present study was to report the late presentation of a case of bilateral BH in an adult and the benefits of chest physiotherapy in the pre-surgical context. It can be concluded that cardiorespiratory reeducation is beneficial in the pre-surgical approach to BH, providing benefits such as improved functional capacity, increased chest expansion, improved quality of life and consequent reduction of surgical risk factors.